New Challenges in Solar Radiation, Modeling and Remote Sensing - Polo, Jesús; Kaskaoutis, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint gathers several works focused on recent and novel research in solar radiation modeling and forecasting where remote sensing techniques and retrieval information is employed as a part of the methodology. The use of machine learning algorithms in solar irradiance modeling and solar power forecasting is included in some of the works here presented. This is a topic with high interest nowadays because of the impact in solar energy deployment and in atmospheric studies as well. The recent improved remote sensing information and available data and the advances in machine learning algorithms have a relevant presence in this reprint indicating the current ad near future path of the contributions in solar radiation modeling.